ISSUES OF FINANCING OF INVESTMENT PROJECTS ON THE BASIS OF SYNDICATE LOANING - Aminova Nilufar Umarboy Qizi, (International Journal of Innovations in Engineering Research and Technology, 2023)
This article examines the current issues of financing investment projects through syndicated lending, analyzes the current state of financing of investment projects implemented in the Republic of Uzbekistan through these syndicated lending instruments and makes recommendations for their improvement. It also highlights the crucial role of attracting investment to boost the economies of countries, the construction and reconstruction of new enterprises equipped with modern equipment and technologies, as well as the creation of new jobs.